Pengaruh Penambahan Tepung Tempe dan Tepung Kelor Terhadap Kandungan Gizi Formula Teko (Tempe Kelor) - Loaloka, Meirina S; Zogara, Asweros Umbu; Adi, Anak Agung Ayu Mirah; Costa, Santa Luciana Da; Niron, Maria F.D.P Kewa (Jurnal Ners, 2024)
Nutrition problems in Indonesia are still a serious health problem with 28,47% of children are in a condition of malnutrition and malnutrition. Efforts to develop materials Nutritious and affordable food is very necessary. This research was conducted to prove The impact of giving skim milk with the substitution of tempeh flour and moringa flour improve nutritional status in children with malnutrition. This research uses design completely randomized, namely with 4 treatments with 1 standard treatment. Based on the results above showed that the addition of tempeh flour and moringa flour had an effect on the levels The nutritional content of the product produced, especially protein, is 3.076. This is due to because the portion of carbohydrates was replaced with tempeh flour and moringa flour, it increased tempe flour and moringa flour are supplemented or added to the teko formula, the protein content in the formula becomes high so the teko formula is Substituted with tempeh flour and moringa flour, it can be consumed by malnourished toddlers can meet their nutritional needs.